Relationship Between Thyroid Autoantibodies and Recurrence of Papillary Thyroid Carcinoma in Children and Adolescents - Huang, Dongmei; Zhi, Jingtai; Zhang, Jinming; Qin, Xuan; Zhao, Jingzhu; Zheng, Xiangqian; Gao, Ming (Frontiers in Oncology, 2022)
Background Numerous studies reported connection between papillary thyroid carcinoma (PTC) and thyroid autoantibody in adults, but few of them have investigated whether there is a similar link in children and adolescents. The purpose of this research was to explore the relationship between clinicopathological features, prognosis and preoperative thyroid peroxidase antibody (TPOAb) as well as thyroglobulin antibody (TgAb) status in children and adolescents with PTC. Methods This study retrospectively reviewed 179 patients of PTC who underwent a thyroidectomy from January 2000 to June 2021 at Tianjin Medical University Cancer Hospital. We compared preoperative TgAb and TPOAb status with the clinicopathological features and prognosis of children and adolescents with PTC in different age groups. Results Patients with positive preoperative TPOAb and TgAb had lower recurrence rate in the younger group (P = 0.006, 0.047, respectively). Patients with positive TPOAb preoperatively had normal level of preoperative Tg and less cervical LNM than patients with negative TPOAb in children and adolescents (P < 0.05). Positive TPOAb preoperatively of PTC patients had a longer median DFS (113.4 months) than negative TPOAb (64.9 months) (P = 0.009, log-rank). Univariate analyses showed age, maximal tumor size, T stage, multifocality, lateral LNM and N staging were predictors for cancer recurrence in children and adolescents (P<0.05). Cox regression analysis found younger age (HR 0.224, P < 0.001), lateral LNM (HR 0.137, P = 0.010), N stage (HR 30.356, P < 0.001) were independent risk factors for recurrence. Conclusions Our study found that presence of preoperative TPOAb and TgAb could serve as novel prognostic factors for predicting recurrence of PTC in children.